2015
DOI: 10.1021/acs.chemmater.5b01347
|View full text |Cite
|
Sign up to set email alerts
|

Low-Impurity High-Performance Solution-Processed Metal Oxide Semiconductors via a Facile Redox Reaction

Abstract: Metal oxide semiconductors realized using solution processes have received a great deal of attention because of their low cost and simple fabrication. One major problem associated with the solution approach is the presence of undesired impurity species introduced by precursor solutions. Here, we investigated the effects of impurities on the electrical properties and device performance of metal oxide semiconductor thin-film transistors. It was found that chlorine residues inhibit the formation of the oxide fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…[14] contributes to a b NO 3 ) 3 -derived I 24.0 cm 2 V -1 s -1 lusion is also s s. [10] l strategy to im irable anions wi portionation bet will not introduc lorine (Cl 2 ), a ctor film. [8] Wi ses the field eff ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[14] contributes to a b NO 3 ) 3 -derived I 24.0 cm 2 V -1 s -1 lusion is also s s. [10] l strategy to im irable anions wi portionation bet will not introduc lorine (Cl 2 ), a ctor film. [8] Wi ses the field eff ( Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…Details can be found in our previous publications. [7,8] For redox reaction, 221.1 mg of indium chloride (InCl 3 , Aldrich, 99.999%) and 0.0861 g of perchloric acid (HClO 4 , Aldrich, ACS reagent, 60%) are added into 10 mL of water. 2-Methoxyethanol (2-ME) solution was synthesized by adding 0.05 mL of ammonium hydroxide (NH 4 OH, 28.0%, Aldrich, 99.99%), 0.05 mL of acetylacetone (AcAc, Aldrich, 99%) and 300 mg of indium nitrate hydrate (In(NO 3 ) 3 ·xH 2 O, Aldrich, 99.999%) into 10 mL 2-ME.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the trade-off between the processing temperature and the performance of solution-processed MO-TFTs remains a great challenge. [4] Several methods for low-temperature, high-performance MO-TFTs have been proposed, such as low-thermal budget processes and new chemical approaches. [4] Low-thermal budget processes provide external energy such as ultraviolet irradiation, [5] microwave annealing, [6] infrared exposure, [7] laser annealing, [8] and high-pressure annealing [9] to reduce the thermal budget.…”
Section: Introductionmentioning
confidence: 99%
“…Rim and Yang et al reported that adding perchloric acid into InCl 3 precursors to eliminate chloridion at low temperature. [4] In addition, Kanatzidis and Facchetti et al reported combustion processes to fabricate MO films at low temperature. [12][13][14] Then, Cho et al reported "self-combustion" method which choice specific metal salt to achieve the combustion reaction without any other addition agents.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the candidate materials, metal oxides are being employed in increasingly diverse applications, such as in display-driving devices, particularly transistors, because of their high electrical performance and thermal and chemical stability under ambient conditions. Solution processing of oxide transistors has been intensively studied in recent years, with several low-temperature (below 250 °C) approaches being developed and device fabrication on flexible substrates being demonstrated123456789.…”
mentioning
confidence: 99%